Determinants of lecturer performance: a multifactorial study at private university in Lampung - Muhammad Muhammad; Chablullah Wibisono; Angelina E. Rumengan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study investigates the multifactorial relationship between motivation, leadership, organizational culture, digital information, and career development with lecturer performance in private universities in Lampung, focusing on competence as a mediator. In the context of increasingly digitized education, this study aims to provide empirical insights into how these factors interact to influence academic performance. This explanatory research combines quantitative and qualitative approaches, using Structural Equation Modelling (SEM) to analyze data from 307 uncertified lecturers in Lampung. The analysis was conducted with SPSS version 26 and SMARTPLS 3.0, and NVIVO 12 Plus to enrich the interpretation of the findings. The results revealed that organizational culture and digital information positively influenced competence, which in turn contributed to improved lecturer performance. Meanwhile, motivation and leadership did not show significant influence directly, but had indirect effects through competence